A novel sustained-release agent based on disulfide-induced recombinant collagen hydrogels for the prevention and treatment of Schistosoma infections - Jie Wang; Lijun Song; Yuntian Xing; Yang Dai; Jinyuan Hu; Guoli Qu; Yongliang Xu; Xuren Yin; Derong Hang; Jianfeng Zhang; Chunrong Xiong; Liang Shi; et al. (Microbiology Spectrum)
ABSTRACT Schistosomiasis is commonly managed using the praziquantel, but it is only effective against adult worms and duration of action is short. Liver fibrosis will worsen if eggs are still present after stopping treatment. Therefore, this study aimed to develop a sustained drug release system for effectively preventing and treating schistosomiasis. A disulfide bond-induced three-dimensional (3D) recombinant collagen hydrogel was developed for sustained praziquantel release. Three collagen sequences were developed based on the sequence for Scl2 of S. pyogene, with different substitutions of residues for cysteine (S-VCL-S1, S-VCL-S2, and S-VCL-S3). Their properties were tested. Mice were infected with Schistosoma japonicum cercariae and treated either with praziquantel collagen hydrogel or niclosamide collagen hydrogel. The worm-killing effect was examined. The application of hydrogel-niclosamide on the skin for 24 h effectively prevented Schistosome cercariae from infecting mice and showed 70.95% and 81.73% reduction in the number of eggs and worms, respectively. The combined use of niclosamide and anti-cercariae cream showed 100% protection after 24 h. The hydrogel-praziquantel also showed a 100% reduction of worms and eggs after 24 h of subcutaneous injection. The subcutaneous injection of praziquantel after 28 days of infection showed 95.19% and 80.12% reduction of worm and egg counts, respectively, and the development of larvae was significantly slowed down. Liver analysis showed no infection after 7 days of treatment. These results suggest developing a novel type of sustained-release agent against schistosomiasis based on the recombinant collagen hydrogel that provides a potential new treatment for schistosomiasis.IMPORTANCEThis study introduces an new way for treating schistosomiasis: a special collagen hydrogel that gradually releases medication to treat schistosomiasis effectively. This innovation provides a promising way to treat schistosomiasis. It represents a significant step forward in the fight against this disease and offers hope for more effective and safer treatments in the future.